3D bioprinting patient-specific grafts for tendon/ligament repair in motion: emerging trends and challenges - Bai, Xuejian; Yang, Yihan; Chu, Jinwei; Deng, Yang; Li, Mingwei; Yang, Huaiyu (Frontiers in Bioengineering and Biotechnology, 2025)
Tendon/ligament (T/L) injuries sustained during motion are highly prevalent and severely impact athletes’ careers and quality of life. Current treatments, including autografts, allografts, and synthetic ligaments, have limitations such as donor site morbidity, immune rejection, and biomechanical mismatch, especially under dynamic loading conditions encountered in motion. 3D bioprinting offers a revolutionary approach for constructing patient-specific T/L grafts. This Mini Review summarizes recent advancements in utilizing 3D bioprinting to fabricate patient-specific grafts for T/L repair, with a particular focus on strategies catering to the functional demands of “in motion” recovery. Key emerging trends in bioink development (balancing mechanical properties with bioactivity), cell selection and optimization, printing strategies (e.g., multi-material hierarchical printing, biomimetic design for complex mechanical loading), and post-printing maturation culture (e.g., multi-modal mechanical stimulation via bioreactors) are discussed. Furthermore, this review highlights critical challenges in the field, including precise matching and long-term maintenance of graft mechanical properties, effective vascularization and innervation, scalable manufacturing and quality control, and hurdles in clinical translation. Finally, this review underscores the immense potential of 3D bioprinting in personalized, functional T/L repair and envisions future research directions, such as the application of smart biomaterials and 4D bioprinting, refined in vitro maturation strategies, and in vivo bioprinting technologies, ultimately aiming to achieve robust tissue functional restoration “in motion.”